1998
DOI: 10.1159/000028664
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chemotherapy inNewly Diagnosed Ependymoma of Childhood

Abstract: The use of chemotherapy in treating children with newly diagnosed ependymoma is currently being investigated, both clinically and experimentally. Assessment of the true efficacy of this modality is hampered by a lack of prospective randomized trials comparing conventional treatment schemes of aggressive surgical excision followed by radiation therapy with or without addition of chemotherapy. Although with current regimens, the role of chemotherapy in newly diagnosed disease appears limited, measurable disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Chemotherapy has not yielded a significant improvement in survival for patients with ependymal tumors. 46,55 High-dose chemotherapy followed by autologous bone marrow transplantation has been tried experimentally. 40 At this point, the data are not sufficient to justify the use of chemotherapy in patients with ependymomas, except in younger children (to substitute for or delay radiation therapy 56 ) or patients in whom surgery and radiation therapy have failed to control tumor growth.…”
Section: Ependymomamentioning
confidence: 99%
“…Chemotherapy has not yielded a significant improvement in survival for patients with ependymal tumors. 46,55 High-dose chemotherapy followed by autologous bone marrow transplantation has been tried experimentally. 40 At this point, the data are not sufficient to justify the use of chemotherapy in patients with ependymomas, except in younger children (to substitute for or delay radiation therapy 56 ) or patients in whom surgery and radiation therapy have failed to control tumor growth.…”
Section: Ependymomamentioning
confidence: 99%
“…5,7,23 The following clinical variables seem to favor long-term survival: 1) adult age; 2) tumors located within the cerebral hemisphere; 3) more benign histological appearance; and 4) total resection. 29 In another retrospective study of 31 children presenting with intracranial ependymomas between 1976 and 1993, it was found that failure at the primary site was the major obstacle to improved cure rates. 27 In a review of 30 patients harboring histologically confirmed posterior fossa ependymomas who underwent surgery at the Mayo Clinic (age range 1-69 years), the following factors were found: 1) younger (Յ 5 years) age was associated with a poorer prognosis; 2) there was a trend toward a better 5-year survival rate with a gross-total resection; 3) tumors recur at the primary intracranial site; and 4) symptomatic spinal seeding does not occur frequently.…”
Section: Prognosis and Survivalmentioning
confidence: 99%
“…Radiation ranging from 3500 to 7200 cGy doses have been given over 5 to 6 weeks. 29 For chemotherapy of ependymomas, the platinum compounds, cisplatin and carboplatin, may be the most effective agents discovered to date. 6 For tumors in the posterior fossa, the recommended dose is 5400 cGy.…”
Section: Surgery Radiation Therapy Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard treatment of MEPN is aggressive surgery. However, tumor recurrence can occur with incomplete resection and the role of adjuvant chemotherapy (25, 36, 37) or radiotherapy (30, 33, 41) is unresolved for the subset of patients with recurrence or in patients in whom gross total resection cannot be achieved.…”
Section: Introductionmentioning
confidence: 99%